Stac3 is required for myotube formation and myogenic differentiation in vertebrate skeletal muscle - Bower, Neil I; de la Serrana, Daniel Garcia; Cole, Nicholas J; Hollway, Georgina E; Lee, Hung-Tai; Assinder, Stephen; Johnston, Ian A (The Journal of biological chemistry, 2012)
Stac3 was identified as a nutritionally regulated gene from an Atlantic salmon subtractive hybridization library with highest expression in skeletal muscle. Salmon Stac3 mRNA was highly correlated with myogenin and myoD1a expression during differentiation of a salmon primary myogenic culture and was regulated by amino acid availability. In zebrafish embryos, stac3 was initially expressed in myotomal adaxial cells and in fast muscle fibers post-segmentation. Morpholino knockdown resulted in defects in myofibrillar protein assembly, particularly in slow muscle fibers, and decreased levels of the hedgehog receptor patched. The function of Stac3 was further characterized in vitro using the mammalian C2C12 myogenic cell line. Stac3 mRNA expression increased during the differentiation of the C2C12 myogenic cell line. Knockdown of Stac3 by RNAi inhibited myotube formation, and microarray analysis revealed that transcripts involved in cell cycle, focal adhesion, cytoskeleton, and the pro-myogenic factors Igfbp-5 and Igf2 were down-regulated. RNAi-treated cells had suppressed Akt signaling and exogenous insulin-like growth factor (Igf) 2 was unable to rescue the phenotype, however, Igf/Akt signaling was not blocked. Overexpression of Stac3, which results in increased levels of Igfbp-5 mRNA, did not lead to increased differentiation. In synchronized cells, Stac3 mRNA was most abundant during the G(1) phase of the cell cycle. RNAi-treated cells were smaller, had higher proliferation rates and a decreased proportion of cells in G(1) phase when compared with controls, suggesting a role in the G(1) phase checkpoint. These results identify Stac3 as a new gene required for myogenic differentiation and myofibrillar protein assembly in vertebrates.